Etching composition for metal radiating fin and preparation method thereof
By using star structure surfactant in the metal heat sink etching process, the problems of etching instability and surface roughness in the wet etching process are solved, and higher manufacturing yield and surface smoothness are achieved.
Patent Information
- Application Number
- CN202411776220.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing wet etching process is difficult to control, and etching perforation defects and deformation are prone to occur, resulting in rough and uneven surface of the metal heat sink and low manufacturing yield.
The star-shaped structure surfactant is used to improve the stability of the etching liquid and the stabilization effect of metal ions through its wetting effect on the surface of the metal material and the protective film generation ability, and reduce the affinity of the etching liquid to the photosensitive glue/metal material interface.
The stability of the wet etching process is improved, the surface roughness of the metal foil after etching is reduced, excessive corrosion of the etching liquid on the metal is avoided, and the manufacturing yield of the metal heat sink is significantly improved.
Smart Images

Figure CN119613296A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of etching and preparing heat sinks, and in particular to an etching composition for metal heat sinks and a preparation method thereof. Background Art
[0002] With the continuous development of electronic technology and communication technology, the requirements for the heat dissipation efficiency of radiators in electronic equipment are getting higher and higher. The main ways to improve the heat dissipation efficiency of radiators include improving the fin efficiency of the heat sink, optimizing the structure of the radiator to improve the flow heat transfer coefficient, etc. Among them, metal heat sinks (fins) are widely used in various types of radiators, and the heat dissipated by the heat sink is proportional to the surface area. Therefore, the industry uses a variety of different processes to increase the surface area of the heat sink to improve the heat dissipation efficiency of the heat sink.
[0003] At present, the most commonly used method to increase the surface area of the heat sink is etching microstructure technology. The surface area of the metal heat sink is increased by etching process to obtain sufficient steam space, thereby improving the heat transfer efficiency of the heat sink. The main etching principle in the copper or copper alloy etching process is the oxidation-reduction chemical reaction between the etching solution and the metal copper. The metal Cu loses electrons and becomes Cu2+ and enters the etching solution. The corresponding chemical reaction equation is expressed as: 2Cu-2e→Cu 2+ .
[0004] However, during the etching process of the metal heat sink, due to the anisotropic characteristics of wet etching, the etching process is difficult to control, and etching perforation defects and deformation problems are very likely to occur. In particular, the etching solution has a poor wetting effect on the surface of the metal sheet. The etching solution is also prone to corroding and penetrating the bonding surface between the photosensitive adhesive and the metal material, resulting in insufficient smoothness of the etched metal surface, resulting in defects such as roughness, particles, and burrs. It is difficult to ensure the manufacturing yield of the metal heat sink, which has become a technical bottleneck problem in the current wet etching process. Summary of the invention
[0005] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a surfactant with a star structure and an etching composition for a metal heat sink using the surfactant. By adding the surfactant with a star structure, the wetting effect of the etching solution on the surface of the metal material is improved, and it can react with the surface of the metal material to form a protective film, increase the stabilizing effect on the metal ions in the etching solution, and reduce the affinity of the etching solution for the photosensitive resin / metal material interface, thereby improving the stability of the wet etching process and the manufacturing yield of the metal heat sink.
[0006] In a first aspect, a star-shaped structure surfactant comprises a core A and linear side chains; wherein the core A is an isocyanate polymer, the linear side chains comprise polyoxyethylene segments and straight-chain alkyl segments, the linear side chains are sequentially connected to the core A, the number of linear side chains is ≥3, a=4-20, and b=4-30;
[0007] Preferably, the number of linear side chains connected to the core A is 3, and the corresponding structure of the star-shaped surfactant is:
[0008]
[0009] Preferably, the structure of the A core comprises or
[0010] Preferably, the R group is selected from alkanes, cycloalkanes, aromatic hydrocarbons or heteroaromatic hydrocarbons having 1 to 30 carbon atoms.
[0011] Preferably, the R group consists of at least one aromatic ring.
[0012] In a second aspect, the preparation method of the star-shaped structure surfactant mentioned above comprises: reacting an alkyl polyoxyethylene alcohol with an isocyanate polymer to obtain the star-shaped structure surfactant.
[0013] Wherein, a catalyst is used in the reaction process of the alkyl polyoxyethylene alcohol and the isocyanate polymer, and the catalyst is selected from an organic tin compound, and preferably, the first catalyst is dibutyltin dilaurate (DBTL for short);
[0014] Preferably, the temperature during the reaction is 60-100°C.
[0015] Preferably, the reaction time is 2 to 6 hours.
[0016] Preferably, the molar ratio of isocyanate groups (-NCO) in the isocyanate polymer to hydroxyl groups (-OH) in the alkyl polyoxyethylene alcohol is 1:(1.0-1.2); more preferably, the molar ratio of isocyanate groups (-NCO) in the isocyanate polymer to hydroxyl groups (-OH) in the alkyl polyoxyethylene alcohol is 1:(1.0-1.05).
[0017] In a third aspect, an etching composition comprises: 1.0-5.0 g / L of the star-shaped structure surfactant described above, 50-70 g / L of hydrogen peroxide, 1-15 g / L of buffer, 30-40 g / L of inorganic acid, 30-50 g / L of organic acid, 0.5-2.5 g / L of sodium thiosulfate, 1.0-5.0 g / L of imidazole, and water is selected as the solvent;
[0018] Preferably, the inorganic acid is selected from: hydrochloric acid, sulfuric acid or nitric acid;
[0019] Preferably, the organic acid is selected from: citric acid, malic acid, oxalic acid or succinic acid;
[0020] Preferably, the buffer is selected from: triethylammonium bicarbonate;
[0021] Preferably, the solvent of the etching composition is deionized water; more preferably, the conductivity of the deionized water is ≤1.0×10 -6 S / cm;
[0022] Preferably, the amount of the star-shaped structure surfactant described above is 1.5 to 4.5 g / L.
[0023] In a fourth aspect, the method for preparing the etching composition described above comprises: firstly dissolving the star-shaped structure surfactant described above in water and then stirring the solution evenly, and then adding other components to the water according to the formula ratio and stirring the solution evenly.
[0024] A fifth aspect is the use of the above etching composition in etching the surface of copper or copper alloy;
[0025] Preferably, the above etching composition is used for etching a copper or copper alloy surface with a thickness not exceeding 1 mm.
[0026] In a sixth aspect, a metal heat sink etching process comprises the following steps:
[0027] S1. Use a film machine to draw a heat sink film and output it. The heat sink film includes two different areas: an exposure area and a non-exposure area.
[0028] S2, taking a metal foil as a raw material for preparing a heat sink, screen-printing a photosensitive adhesive on both sides of the metal foil, and drying;
[0029] S3, aligning the heat sink film in step S1 with the metal foil printed with photosensitive adhesive layers on both sides in step S2, and exposing them;
[0030] S4, developing and drying the metal foil after the exposure treatment in step S3;
[0031] S5, etching the metal foil after the development treatment in step S4, and etching it by immersion etching using the etching solution composition described above;
[0032] S6, developing the metal foil after being etched in step S5 to remove the photosensitive resin remaining on the surface.
[0033] Preferably, the drying process after screen printing in step S2 includes: placing in an oven at a temperature not higher than 40° C. and drying for 60 to 300 seconds;
[0034] Preferably, the exposure process of step S3 includes: exposing it using a high-pressure mercury lamp, wherein the exposure power is not less than 25mj / cm2 , the exposure time is not less than 10s;
[0035] Preferably, the post-development drying process in step S4 includes: first removing surface moisture and then placing in an oven at 80 to 95° C. for drying for 5 to 60 minutes;
[0036] Preferably, the immersion etching time of step S5 is 60 to 300 seconds, and more preferably, the immersion etching time of step S5 is 60 to 120 seconds;
[0037] Preferably, in step S6, a developer is used to develop the etched metal foil.
[0038] In a seventh aspect, a metal heat sink is prepared using the etching process described above.
[0039] The beneficial effects of the technical solution proposed by the present invention are:
[0040] By designing and synthesizing a star-shaped structure surfactant, the core of which includes one or more aromatic rings containing π bonds, and the linear side chains include polyoxyethylene segments and straight-chain alkyl segments, wherein the aromatic rings and polyoxyethylene segments can interact with the empty orbits of metal atoms, thereby forming adsorption sites on the surface of the metal sheet. The surfactant is added to the water-based etching liquid composition, which can not only improve the wettability of the etching liquid on the metal surface, but also adsorb on the surface of the metal material during the etching process and form a protective film, which plays a role in stabilizing the metal ions in the etching liquid and improving the stability of the etching process, especially in reducing the surface roughness of the metal foil after etching, avoiding the bottom of the metal sheet from being corroded due to the high corrosion rate of the etching liquid on the metal during the etching process, and the defects such as roughness, particles, and burrs on the surface of the metal sheet, thereby improving the manufacturing yield of the metal heat sink. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The star-shaped surfactant prepared in Example 1 13 C-NMR spectrum.
[0042] Figure 2 The star-shaped surfactant prepared in Example 3 13 C-NMR spectrum.
[0043] Figure 3 This is the equivalent circuit diagram used when fitting the electrochemical impedance spectroscopy data.
[0044] Figure 4 Nyquist plot of electrochemical impedance spectroscopy.
[0045] Figure 5 Bode-Phase angle diagram of electrochemical impedance spectroscopy.
[0046] Figure 6 The SEM images of Examples 13 and 14 and Comparative Examples 3 and 4 are shown, wherein (a) is the copper alloy heat sink prepared in Example 13; (b) is the copper alloy heat sink prepared in Example 14; (c) is the copper alloy heat sink prepared in Comparative Example 1; and (d) is the copper alloy heat sink prepared in Comparative Example 2. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0048] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0049] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.
[0050] Example 1
[0051] In a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 174g of diisocyanate TDI-80 was added, and 1.8g (1mol) of water was added as a reactant. The temperature was raised to 110°C for reaction for 2 hours and then continued to rise to 130°C. The reaction continued at 130°C until the conversion rate of the NCO group exceeded 15%, and then the temperature was lowered to stop the reaction. The reaction mixture was subjected to reduced pressure distillation to remove unreacted monomers, thereby preparing 155.6g of TDI trimer. The TDI trimer was subjected to nuclear magnetic resonance carbon spectroscopy to verify the presence of a biuret structure. The data of the nuclear magnetic resonance carbon spectroscopy are as follows: 13C-NMR (CDCl3): δ19.37 (3C, s), 119.05 (2C, s), 119.91 (2C, s), 125.22 (3C, s), 126.35 (3C, s), 130.42 (1C, s), 131.53 (1C, s), 132.57 (3C, s), 137.61 (3C, s), 137.22 (1C, s), 139.26 (2C, s), 157.48 (2C, s), 172.25 (1C, s). The carbon atoms corresponding to the two displacements at 157.48 and 172.25 in the carbon spectrum indicate that the surfactant molecule prepared in Example 1 contains the biuret structure shown below.
[0052]
[0053] The reaction raw material AEO-7 (lauryl polyoxyethylene ether) was dehydrated under reduced pressure at 100°C for 3 hours, then 99g (0.20mol) of the dehydrated AEO-7 was weighed, 104.3g (0.21mol) of TDI trimer and 1.0g of catalyst DBTL were added, and the temperature was raised to 85°C under nitrogen protection for 4 hours, and then a small amount of unreacted monomers were recovered by reduced pressure distillation at 0.01MPa and 80°C.
[0054] Example 2
[0055] In a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 250 g of diisocyanate MDI-50 was added, and 1.8 g (1 mol) of water was added as a reactant. The temperature was raised to 100° C. and reacted for 2 hours, then the temperature was continuously raised to 130° C. The reaction was continued at 130° C. until the conversion rate of the NCO group exceeded 15%, and then the temperature was lowered to stop the reaction. The reaction mixture was subjected to reduced pressure distillation to remove unreacted monomers, thereby preparing 234.8 g of MDI trimer.
[0056] The reaction raw material AEO-7 (lauryl polyoxyethylene ether) was dehydrated under reduced pressure at 100°C for 3 hours, then 99g (0.20mol) of the dehydrated AEO-7 was weighed, 152.2g (0.21mol) of TDI trimer and 1.0g of catalyst DBTL were added, and the temperature was raised to 85°C under nitrogen protection for 4 hours, and then a small amount of unreacted monomers were recovered by reduced pressure distillation at 0.01MPa and 80°C.
[0057] Example 3
[0058] In a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 174g of diisocyanate TDI-80 was added, 160mL of butyl acetate was added as a solvent, 0.7g of 2-hydroxypropyltrimethylammonium formate (TMR-2) was added as a reaction catalyst, and the reaction was carried out at 70°C until the conversion rate of the NCO group exceeded 20%, and then 0.29g of phosphoric acid H3PO4 was added to the flask to terminate the reaction. The reaction mixture was subjected to reduced pressure distillation to remove unreacted monomers, thereby preparing 152.6g of TDI trimer. The TDI trimer was subjected to nuclear magnetic resonance carbon spectrum to verify the presence of a nitrogen heterocyclic structure, and the data of nuclear magnetic resonance carbon spectrum are as follows: 13 C-NMR (CDCl3) δ19.44 (3C, s), 116.07 (2C, s), 117.13 (1C, s), 117.71 (2C, s), 123.81 (1C, s), 124.95-125.05 (3C, s), 126.38 (2C, s), 132.42 (2C, s), 132.57 (1C, s), 134.87 (1C, s), 137.06 (2C, s), 141.69 (1C, s), 144.32 (2C, s), 151.63 (3C, s). The carbon atom corresponding to the displacement at 151.63 in the carbon spectrum and the integral of the carbon atom are 3, which shows that the surfactant molecule prepared in Example 3 has the following carbon-nitrogen heterocyclic structure
[0059]
[0060] The reaction raw material AEO-7 (lauryl polyoxyethylene ether) was dehydrated under reduced pressure at 100°C for 3 hours, then 99g (0.20mol) of the dehydrated AEO-7 was weighed, 109.7g (0.21mol) of TDI trimer and 1.0g of catalyst DBTL were added, and the temperature was raised to 85°C under nitrogen protection for 4 hours, and then a small amount of unreacted monomers were recovered by reduced pressure distillation at 0.01MPa and 80°C.
[0061] Example 4
[0062] In a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 250 g of diisocyanate MDI-50, 220 mL of butyl acetate as a solvent, and 1.0 g of 2-hydroxypropyltrimethylammonium formate (TMR-2) as a reaction catalyst were added, and the reaction was carried out at 60° C. The reaction was continued until the conversion rate of the NCO group exceeded 20%, and then 0.42 g of phosphoric acid H3PO4 was added to the flask to terminate the reaction. The reaction mixture was subjected to reduced pressure distillation to remove unreacted monomers, thereby preparing 226.9 g of MDI trimer.
[0063] The reaction raw material AEO-7 (lauryl polyoxyethylene ether) was dehydrated under reduced pressure at 100°C for 3 hours, then 99g (0.20mol) of the dehydrated AEO-7 was weighed, 157.7g (0.21mol) of MDI trimer and 1.3g of catalyst DBTL were added, and the temperature was raised to 85°C under nitrogen protection for 4 hours, and then a small amount of unreacted monomers were recovered by reduced pressure distillation at 0.01MPa and 80°C.
[0064] Example 5
[0065] The etching liquid composition was prepared according to the following raw materials: 55 g / L hydrogen peroxide, 11.5 g / L triethylammonium bicarbonate, 34 g / L nitric acid, 40 g / L citric acid, 1.0 g / L sodium thiosulfate, 1.8 g / L imidazole, and 2.5 g / L surfactant of Example 1. The solvent of the etching liquid composition was deionized water (conductivity of deionized water was 0.56×10 -6 The surfactant of Example 1 was dissolved in deionized water and stirred for 10 minutes to prepare a 2.5 g / L surfactant aqueous solution. Other components were added under stirring and stirred for 10 minutes to prepare an etching solution composition.
[0066] Example 6
[0067] The surfactant was replaced by the surfactant prepared in Example 2, with an amount of 2.5 g / L, and the remaining formula ratios and preparation steps were the same as in Example 5.
[0068] Example 7
[0069] The surfactant was replaced by the surfactant prepared in Example 3, with an amount of 2.5 g / L, and the remaining formula ratios and preparation steps were the same as in Example 5.
[0070] Example 8
[0071] The surfactant was replaced by the surfactant prepared in Example 4, with an amount of 2.5 g / L, and the remaining formula ratios and preparation steps were the same as in Example 5.
[0072] Example 9
[0073] The etching liquid composition was prepared according to the following raw materials: 60 g / L hydrogen peroxide, 11.5 g / L triethylammonium bicarbonate, 36 g / L nitric acid, 40 g / L citric acid, 1.0 g / L sodium thiosulfate, 1.8 g / L imidazole, and 4.5 g / L surfactant of Example 4. The solvent of the etching liquid composition was deionized water (conductivity of deionized water was 0.56×10 -6The surfactant of Example 1 was dissolved in deionized water and stirred for 10 minutes to prepare a 4.5 g / L surfactant aqueous solution. Other components were added under stirring and stirred for 10 minutes to prepare an etching solution composition.
[0074] Example 10
[0075] The etching liquid composition was prepared according to the following raw materials: 60 g / L hydrogen peroxide, 11.5 g / L triethylammonium bicarbonate, 32 g / L nitric acid, 40 g / L citric acid, 1.0 g / L sodium thiosulfate, 1.8 g / L imidazole, and 1.5 g / L surfactant of Example 4. The solvent of the etching liquid composition was deionized water (conductivity of deionized water was 0.56×10 -6 The surfactant of Example 1 was dissolved in deionized water and stirred for 10 min to prepare a 1.5 g / L surfactant aqueous solution. Other components were added under stirring and stirred for 10 min to prepare an etching solution composition.
[0076] Embodiment 11
[0077] The preparation of the copper alloy heat sink is carried out according to the following steps:
[0078] S1. Use a film machine to draw a heat sink film and output it. The heat sink film includes two different areas: an exposure area and a non-exposure area.
[0079] S2, taking a copper alloy foil with a thickness of 1 mm as a raw material for preparing a heat sink, screen-printing Komet PLUS8000 photosensitive adhesive on the upper and lower surfaces of the copper alloy foil, and drying it in a 40°C oven for 120 seconds to obtain a copper alloy foil with photosensitive adhesive layers printed on both sides;
[0080] S3, align the heat sink film of step S1 with the copper alloy foil printed with photosensitive adhesive layers on both sides in step S2, and expose them using a high-pressure mercury lamp with an exposure wavelength of 365nm and an exposure power of 45mj / cm 2 , exposure time 18s, the corresponding photosensitive resin part on the surface of the copper alloy heat sink is exposed through the exposure area in the heat sink film;
[0081] S4, the copper alloy foil after the exposure treatment in step S3 is rinsed and developed at a uniform speed using a high-pressure spray gun, and after development, surface moisture is removed and then placed in an 80° C. oven for drying for 15 minutes;
[0082] S5, etching the copper alloy foil after the development treatment in step S4, using the etching solution prepared in Example 5 for immersion etching, and the immersion time is 90 seconds;
[0083] S6. Using a developer KBX-205 to remove the photosensitive resin remaining on the surface of the copper alloy heat sink after etching in step S5, thereby obtaining a prepared copper alloy heat sink.
[0084] Example 12
[0085] The etching process of step S5 adopts the etching solution prepared in Example 6 for immersion etching, and the immersion time is 90 seconds. The remaining steps are the same as those in Example 11.
[0086] Example 13
[0087] The etching process of step S5 adopts the etching solution prepared in Example 7 for immersion etching, and the immersion time is 90s. The remaining steps are the same as those in Example 11.
[0088] Embodiment 14
[0089] The etching process of step S5 adopts the etching solution prepared in Example 8 for immersion etching, and the immersion time is 90s. The remaining steps are the same as those in Example 11.
[0090] Embodiment 15
[0091] The etching process of step S5 adopts the etching solution prepared in Example 9 for immersion etching, and the immersion time is 100 seconds. The remaining steps are the same as those in Example 11.
[0092] Example 16
[0093] The etching process of step S5 adopts the etching solution prepared in Example 10 for immersion etching, and the immersion time is 80 seconds. The remaining steps are the same as those in Example 11.
[0094] Comparative Example 1
[0095] The surfactant was changed to dodecylaminopropionic acid in an amount of 2.5 g / L, and the remaining formula proportions and preparation steps were the same as in Example 5.
[0096] Comparative Example 2
[0097] The surfactant was changed to polyethylene glycol oleate diester in an amount of 2.5 g / L, and the remaining formula ratios and preparation steps were the same as in Example 5.
[0098] Comparative Example 3
[0099] The etching process of step S5 adopts the etching solution prepared in comparative example 1 for immersion etching, and the immersion time is 90s. The remaining steps are the same as those in embodiment 11.
[0100] Comparative Example 4
[0101] The etching process of step S5 adopts the etching solution prepared in comparative example 2 for immersion etching, and the immersion time is 90s. The remaining steps are the same as those in embodiment 11.
[0102] Test Section
[0103] Electrochemical impedance test: A three-electrode system was used to perform electrochemical impedance spectroscopy (EIS) testing using a Chi660e electrochemical workstation. Copper foil was used as the working electrode, the reference electrode was a mercury / mercurous sulfate electrode, and a platinum electrode was used as the counter electrode. Before the experiment, the working electrode was polished with 800-mesh sandpaper and then cleaned twice with ethanol and deionized water. During the experiment, an electrochemical three-electrode system was first built, and the electrochemical impedance spectroscopy test was performed after the open circuit potential was stabilized. The electrochemical experimental solution is the etching solution prepared in Examples 5-8 and Comparative Examples 1-2.
[0104] The electrochemical impedance test firstly tests the open circuit potential. After 300s, the impedance test is performed after the open circuit potential stabilizes. The initial potential is the open circuit potential value recorded previously. The frequency range of the impedance test is 10 -2 Hz~10 5 Hz, signal amplitude was 10mV. Using ZView software and Figure 3 The equivalent circuit diagram shown is used to fit the impedance experimental data recorded in the test, and the electrochemical impedance parameters R obtained by different etching solutions are calculated. s With R ct , where R s is the solution resistance of the etching solution between the working electrode and the reference electrode, R ct It is the charge transfer resistance, and its value is used to characterize the resistance encountered by the working electrode when it is corroded by the etching solution.
[0105] Surface morphology analysis of copper alloy heat sink: The copper alloy foil sample was immersed in the copper alloy heat sink prepared in Examples 13 and 14 and Comparative Examples 3 and 4, and the surface morphology of the copper alloy foil was observed using a scanning electron microscope (SEM) after being immersed in the etching solution for 90 seconds.
[0106] Surface roughness test of copper alloy heat sink: MarSurfM 400 portable surface roughness tester was used to measure the surface roughness of the copper alloy heat sink prepared by etching in Examples 11-16 and Comparative Examples 3 and 4. The line roughness R a Characterize the surface roughness of the copper alloy heat sink, and calculate the line roughness R of the copper alloy heat sink by the following formula a .
[0107] Among them, N corresponds to the data point on the X axis, Z is the surface height relative to the reference line, and the line roughness R a The arithmetic mean of the 6 results is taken.
[0108] The electrochemical impedance parameter fitting results of Comparative Examples 1 and 2 and Examples 5-8 are shown in Table 1.
[0109] The calculation results of Comparative Examples 3, 4 and Examples 11-16 are shown in Table 2.
[0110] Table 1
[0111] <![CDATA[Solution resistance R s (Ω / cm 2 )]]> <![CDATA[Charge transfer resistance R ct (Ω / cm 2 )]]> Comparative Example 1 4.63 19.09 Comparative Example 2 7.05 31.42 Example 5 6.99 39.54 Example 6 7.09 43.67 Example 7 7.68 44.33 Example 8 7.46 47.23
[0112] The Nyquist plot and Bode-Phase angle plot of the working electrode (copper foil) in the etching solution prepared in Comparative Examples 1, 2 and Examples 5-8 as electrochemical experimental solutions are shown in the figure below. Figure 4 , 5 As shown. Figure 4 It can be seen from the Nyquist plot that the corrosion electrochemical impedance spectrum of the working electrode in the etching solution shows a semicircular capacitive arc, wherein the larger the radius of the capacitive arc, the larger the corresponding impedance value and the charge transfer resistance, and the value of the charge transfer resistance is directly correlated with the corrosion rate of the etching solution on the working electrode. It can be inferred that the etching solutions of Examples 5-8 have obvious corrosion inhibition effects on the copper electrode under the condition of adding the surfactant prepared in Examples 1-4, and the capacitive arcs of Comparative Examples 1 and 2 are significantly smaller than those of Examples 5-8, which indicates that the charge transfer resistance of Comparative Examples 1 and 2 is lower, and the corrosion rate of the etching solution on the working electrode is faster.
[0113] This point from Figure 5 It can also be seen from the Bode-Phase angle diagram that compared with Comparative Examples 1 and 2, the impedance value and phase angle value of the Bode-Phase angle diagram corresponding to Examples 5-8 increase more significantly, indicating that after adding the surfactant prepared in Examples 1-4, the etching solution prepared in Examples 5-8 can form a dense protective film on the surface of the working electrode, thereby inhibiting the corrosion of the copper surface by the etching solution, and has a significant inhibitory effect on the electrochemical reaction charge transfer process of the corrosion process. The etching solution of Comparative Examples 1 and 2 does not add the corresponding surfactant, resulting in the etching rate of the etching solution on the working electrode being significantly higher than that of Examples 5-8.
[0114] The fitting data recorded in Table 1 also show that the addition of the surfactant prepared in Example 1-4 to Examples 5-8 can play a corrosion inhibition effect and reduce the corrosion rate of the etching solution on the working electrode. The charge transfer resistance R corresponding to the etching solution of Examples 5-8 is ct It is significantly higher than that of Comparative Examples 1 and 2, which indicates that it has higher corrosion resistance and lower corrosion rate to the working electrode.
[0115] It is speculated that the surfactants in Examples 1-4 interact with the empty orbitals of metallic copper through the -NH- of carbamate, the ether bond -O- of the polyether side chain, and the π electrons in the aromatic ring, thereby generating adsorption sites for the surfactants on the surface of the working electrode. As a result, the surfactants are adsorbed on the surface of the copper electrode through the adsorption sites in the etching solution, thereby reducing the corrosion rate of the etching solution on the working electrode.
[0116] Table 2
[0117] <![CDATA[Line roughness R a > Comparative Example 3 1.50 Comparative Example 4 0.83 Embodiment 11 0.33 Example 12 0.23 Example 13 0.20 Embodiment 14 0.17 Embodiment 15 0.25 Example 16 0.17
[0118] It can be seen from the data in Table 2 that the copper alloy foil heat sinks of Examples 11-16 are etched with the etching solution of Examples 5-8 during the preparation process, and the heat sink surface obtained thereby is flatter and smoother, with lower roughness and higher precision, and can significantly reduce the lateral corrosion at the bottom of the heat sink, avoiding the corrosion of the copper alloy sheet surface by the etching solution during the etching process, resulting in defects such as roughness, particles, and burrs, thereby improving the manufacturing yield of the heat sink. This is because the etching solution of Examples 5-8 adds the surfactant prepared by Examples 1-4, and the surfactant contains an aromatic ring core, a polyoxyethylene ether side chain, and an alkyl side chain. In addition to the conventional effect of the surfactant to improve the wettability of the water-based etching solution on the surface of the copper alloy sheet, it also generates adsorption sites on the surface of the copper alloy sheet to generate a protective film, which increases the resistance to Cu in the etching solution. 2+ The stabilizing effect reduces the corrosion rate of the etching solution on the copper alloy and the affinity for the photosensitive resin / copper alloy interface. The heat sink surface smoothness prepared by the etching process of Examples 11-16 is higher, and the etching process of the etching solution on the copper alloy sheet is more effectively controlled to avoid etching perforation defects and deformation. Figure 6 It can also be intuitively seen from the SEM images that, compared with Comparative Examples 3 and 4, the surfaces of the copper alloy sheets prepared in Examples 13 and 14 are significantly smoother.
[0119] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.
Claims
1. A star-shaped surfactant, characterized in that: The star-shaped structure surfactant comprises a core A and linear side chains; wherein the core A is an isocyanate polymer, the linear side chains comprise polyoxyethylene segments and straight-chain alkyl segments, the linear side chains are sequentially connected to the core A, the number of linear side chains is ≥3, a=4-20, and b=4-30; Preferably, the R group consists of at least one aromatic ring.
2. The star-shaped surfactant according to claim 1, characterized in that: The number of linear side chains connected to the core A is 3, and the corresponding structure of the star-shaped surfactant is: Preferably, the structure of the A core comprises or 3. The method for preparing the star-shaped surfactant according to any one of claims 1 to 2, characterized in that: The preparation method comprises: reacting alkyl polyoxyethylene alcohol with isocyanate polymer to obtain; Wherein, a catalyst is used in the reaction process of the alkyl polyoxyethylene alcohol and the isocyanate polymer, and the catalyst is selected from organic tin compounds.
4. The preparation method according to claim 3, characterized in that: The molar ratio of isocyanate groups (-NCO) in the isocyanate polymer to hydroxyl groups (-OH) in the alkyl polyoxyethylene alcohol is 1:(1.0-1.2); preferably, the molar ratio of isocyanate groups (-NCO) in the isocyanate polymer to hydroxyl groups (-OH) in the alkyl polyoxyethylene alcohol is 1:(1.0-1.05).
5. An etching composition, characterized in that The etching composition comprises: 1.0-5.0 g / L of the star-shaped structure surfactant according to any one of claims 1 to 2, 50-70 g / L of hydrogen peroxide, 1-15 g / L of buffer, 30-40 g / L of inorganic acid, 30-50 g / L of organic acid, 0.5-2.5 g / L of sodium thiosulfate, 1.0-5.0 g / L of imidazole, and water is selected as the solvent; Preferably, the inorganic acid is selected from: hydrochloric acid, sulfuric acid or nitric acid; Preferably, the organic acid is selected from: citric acid, malic acid, oxalic acid or succinic acid; Preferably, the buffer is selected from: triethylammonium bicarbonate; Preferably, the star-shaped structure surfactant is used in an amount of 1.5 to 4.5 g / L.
6. The etching composition according to claim 5, characterized in that The solvent of the etching composition is deionized water; preferably, the conductivity of the deionized water is ≤1.0×10 -6 S / cm.
7. The method for preparing the etching composition according to any one of claims 5 to 6, characterized in that: The preparation method comprises: firstly dissolving a star-shaped structure surfactant in water and then stirring the solution evenly, and then adding other components into the water according to the formula ratio and then stirring the solution evenly.
8. Use of the etching composition according to any one of claims 5 to 6 in etching the surface of copper or copper alloy; Preferably, the etching composition according to any one of claims 5 to 6 is used for etching a copper or copper alloy surface with a thickness not exceeding 1 mm.
9. An etching process for a metal heat sink, characterized in that: The etching process comprises the following steps: S1. Use a film machine to draw a heat sink film and output it. The heat sink film includes two different areas: an exposure area and a non-exposure area. S2, taking a metal foil as a raw material for preparing a heat sink, screen-printing a photosensitive adhesive on both sides of the metal foil, and drying; S3, aligning the heat sink film in step S1 with the metal foil printed with photosensitive adhesive layers on both sides in step S2, and exposing them; S4, developing and drying the metal foil after the exposure treatment in step S3; S5, etching the metal foil after the development treatment in step S4, by immersion etching using the etching composition according to any one of claims 5 to 6; S6, developing the metal foil after being etched in step S5 to remove the photosensitive resin remaining on the surface. Preferably, the drying process after screen printing in step S2 includes: placing in an oven at a temperature not higher than 40° C. and drying for 60 to 300 seconds; Preferably, the exposure process of step S3 includes: exposing it using a high-pressure mercury lamp, wherein the exposure power is not less than 25mj / cm 2 , the exposure time is not less than 10s; Preferably, the post-development drying process in step S4 includes: first removing surface moisture and then placing in an oven at 80 to 95° C. for drying for 5 to 60 minutes; Preferably, the immersion etching time of step S5 is 60 to 300 seconds, and more preferably, the immersion etching time of step S5 is 60 to 120 seconds; Preferably, in step S6, a developer is used to develop the etched metal foil.
10. A metal heat sink prepared using the etching process as claimed in claim 9.
Citation Information
Patent Citations
Fluorinated ethoxylated polyurethanes
CN103080176A
Method for preparing radiating fins by etching different thicknesses
CN111465277A